2019
DOI: 10.1101/19012021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common variants in Alzheimer’s disease: Novel association of six genetic variants with AD and risk stratification by polygenic risk scores

Abstract: BACKGROUND:Disentangling the genetic constellation underlying Alzheimer's disease (AD) is important. Doing so allows us to identify biological pathways underlying AD, point towards novel drug targets and use the variants for individualised risk predictions in disease modifying or prevention trials. In the present work we report on the largest genome-wide association study (GWAS) for AD risk to date and show the combined utility of proven AD loci for precision medicine using polygenic risk scores (PRS). METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 64 publications
0
55
0
Order By: Relevance
“…In recent years, genome-wide association studies (GWASs) reinforce that AD is a complex disease, in which APP processing and immune response play key roles [212]. Whole genome sequencing (WGS), GWAS, and gene-expression network analysis proved that LOAD genetics implicates microglial pathways and CR1, SII1, MS4As, TREM2, ABCA7, CD33, INPP5D genes are associated with disease risk [212]. The results of the largest meta-GWAS approach (analyzing 19,089 AD cases) and follow-up analysis for AD risk has been published very recently [212].…”
Section: Genetic Risk Factors Of Ad: Classical Studies and Novel Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, genome-wide association studies (GWASs) reinforce that AD is a complex disease, in which APP processing and immune response play key roles [212]. Whole genome sequencing (WGS), GWAS, and gene-expression network analysis proved that LOAD genetics implicates microglial pathways and CR1, SII1, MS4As, TREM2, ABCA7, CD33, INPP5D genes are associated with disease risk [212]. The results of the largest meta-GWAS approach (analyzing 19,089 AD cases) and follow-up analysis for AD risk has been published very recently [212].…”
Section: Genetic Risk Factors Of Ad: Classical Studies and Novel Resultsmentioning
confidence: 99%
“…Whole genome sequencing (WGS), GWAS, and gene-expression network analysis proved that LOAD genetics implicates microglial pathways and CR1, SII1, MS4As, TREM2, ABCA7, CD33, INPP5D genes are associated with disease risk [212]. The results of the largest meta-GWAS approach (analyzing 19,089 AD cases) and follow-up analysis for AD risk has been published very recently [212]. It was found that altogether 39 genetic variants may be associated with AD risk (beyond the APOE variants).…”
Section: Genetic Risk Factors Of Ad: Classical Studies and Novel Resultsmentioning
confidence: 99%
“…However, previous studies to determine roles of GWAS genes in AD have primarily been limited to the B6 genetic background. Therefore, we aimed to determine whether our wild-derived AD panel provided an enhanced platform to study human-relevant AD genes using a panel of 54 GWAS genes identified in two recent meta-analyses ( Supplementary Table 6 ) 31,32 . A total of 36 microglia-relevant genes were detectable across our panel.…”
Section: Resultsmentioning
confidence: 99%
“…The human AD GWAS genes were selected from two recent meta-analyses (Table 1 31 and Table S2 32 ). The GWAS genes from both tables were combined and were overlapped with equivalent mouse genes in scRNA-seq data from this study.…”
Section: Methodsmentioning
confidence: 99%
“…Apolipoprotein ε4 allele (APOE4) is the only common high risk genetic variant (odds ratio (OR)=3.32) (11,12). Genome wide association studies (GWAS) have further identified many common genetic variants with low risk (OR=1.1-1.2) of which 40 have genome wide significance (12)(13)(14). Exome chip analyses have additionally yielded rare variants in the very same genes, i.e.…”
Section: The Heritability Of Admentioning
confidence: 99%